Potential Selection of Arbuscular Mycorrhizal Fungi (AMF) Indigenous Ultisols through the Production of Glomalin - Eddiwal, .; Saidi, Amrizal; Lenin, Ismon; Husin, Eti Farda; Rasyidin, Azwar (JOURNAL OF TROPICAL SOILS, 2014)
The arbuscular mycorrhizal fungi ( AMF ) with plants able to increase the capacity of plants to absorb nutrients and water from the soil. Recently, research was indicated that AMF hyphae containing glomalin as a glycoprotein that serves to unify the dispersed soil particles. The content of glomalin in soil is positively correlated with soil aggregate stability. The research potential of AMF species indigenous of Ultisol Darmasraya District of West Sumatra and glomalin production in experimental pots of sterile sand medium has been carried out. The purpose of this study was to determine the diversity of AMF species on Ultisol and to seeking indigenous AMF isolates that had the best glomalin production capability. AMF spores were isolated and identified from the rhizosphere soil of corn in Ultisol. AMF species that had been identified experimentally were tested in culture medium pot of sand and zeolite (w / w 1:1) using corn crops. The results found nine of the AMF species indigenous of Ultisol Darmasraya, namely Acaulospora scrobiculata, Glomus etunicatum, Glomus luteum, Glomus mosseae, Glomus verruculosum, Glomus versiforme, Scutellospora gregaria, Scutellospora heterogama and Gigaspora sp. AMF species that showed better colonization ability in corn was G. luteum, G. verruculosum and G. versiforme. All three species produced glomalin significantly higher than the other species, i.e. 1.29 mg g-1; 1.17 mg g-1; 1.15 mg g-1, respectively. [How to Cite: Eddiwal, A Saidi, I Lenin, EF Husin and A Rasyidin. 2014. Potential Selection of Arbuscular Mycorrhizal Fungi (AMF) Indigenous Ultisols through the Production of Glomalin. J Trop Soils 19: 181-189. Doi: 10.5400/jts.2014.19.3.181]Â  Â